A-MMLQ Algorithm for Multi-level Queue Scheduling - Hasija, Manupriya; Kaushik, Akhil; Kumar, Parveen (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
This being the era of advancement in computing domain, the emphasis is on better resource scheduling. Scheduling is not confined to dealing multiple tasks by a single processor. It’s a dawn with multiprocessing and multitasking. Although multiprocessor systems impose several overheads but still make the concept amazingly interesting. The scheduling field has taken a whirlwind after the notion of multiprocessing. Many of the uniprocessor algorithms do fit well under the multiprocessor systems but, still necessitating a further development aiming solely on multiprocessor scheduling. This paper thus sketches a new idea to modify and extend the well-known multi-level queue scheduling, taking into account the arrival time/ arrival sequence to conceptualize an innovative scheduling algorithm.